PENGUATAN WORD OF MOUTH MELALUI STRATEGI INTERNAL BRANDING DI PERGURUAN TINGGI SWASTA INDONESIA - Farida .; Herry Agung Prabowo; Diah Wardhani; Achmad Husnur (Universitas Mercu Buana, 2019)
The purpose of this research is to generate a mapping the level of internal customer internalization of the PTS brands based on intellectual commitment and emotional commitment, as well as its influence on the power of WOM. The sample used is PTS' lecturer in Jakarta area as internal customer. Measurement of brand internalization in this research through the assessment of intellectual commitment, and emotional commitment of lecturers to PTS' brand. Data were collected through answers from questionnaires containing sample opinions on research variables. While the model of the influence of intellectual commitment and emotional commitment to WOM is done by using the model of Structural Equation Model (SEM) processed using the PLS program. The result of this research concludes that the lecturer is in the segment of brand activist. Another result of this research is intellectual commitment and emotional commitment are statistically significant influence on WOM. So that the WOM strength of the lecturer, can be built through the improvement of brand understanding, brand trust and brand delivery lecturers.